Coupling near‐surface geomorphology with mangrove community diversity at the estuarine scale: A case study at Dongzhaigang Bay, China. Issue 1 (30th September 2022) - Chen, Guogui; Hong, Wei; Gu, Xuan; Krauss, Ken W.; Zhao, Kaiyuan; Fu, Haifeng; Chen, Luzhen; Wang, Mao; Wang, Wenqing
ABSTRACT: Coastal wetlands are key features of the Earth's surface and are characterized by a diverse array of coupled geomorphological and biological processes. However, the links between the distribution of biodiversity (for example, species and structural diversity) and the formation of coastal geomorphology are not well‐understood on a landscape scale most useful to coastal zone managers. This study describes the relationship between select geomorphological and biological mangrove community features (i.e. species composition and functional root type) in a landscape‐distributed coastal zone of Dongzhaigang Bay, north‐eastern Hainan Island, China. A total of 11 mangrove species and five functional aerial root types were encountered, with the location of species by root types being controlled by the elevation of the soil surface. Plank roots, prop roots and pneumatophores occupied the lowest intertidal elevations, while knee roots and fibrous roots of the mangrove fern, Acrostichum aureum, preferred the highest intertidal elevations. Surface sediment deposition in areas with mangroves was greater than deposition in non‐mangrove forest zones, establishing an important biological mechanism for this large‐area response because surface erosion/compaction was also more prominent within mangrove roots. Indeed, functional root type influenced the magnitude of deposition, erosion and compaction, with knee roots and pneumatophores being more effective in promoting deposition and preventing surface erosion/compaction than prop roots. These results indicate a potential role for vegetation type (especially functional root type) to influence coastal geomorphological processes at large landscape scales. While soil surface elevation is correlated to the distribution of mangrove species and functional root types, a significant feedback exists between elevation change and the capacity of those root types to influence coastal geomorphological differentiation within sustainable intertidal elevations. An enhanced understanding of geomorphological development, mangrove species distribution and functional root type may improve management to support nature‐based solutions that adjust more effectively to sea‐level rise through feedbacks.